2016
DOI: 10.1055/s-0036-1580714
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medicinal Plants with Teratogenic and Abortive Effects by Pregnant Women in a City in Northeastern Brazil

Abstract: The health of the study participants and their unborn children is at risk due to the inappropriate use of medicinal plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
1
15
2
2
Order By: Relevance
“…With respect to the use of alternative therapies, 31.0% of pregnant women in Brum et al (2011) and 30.9% in Araújo et al (2016) reported the use of medicinal plants, whereas in our study this was 26.6%resulting in an average of 0.5 medicinal plants being used by the pregnant women. In a study by Mengue et al (2001), phytotherapics were used in 55 cases (0.6%), products composed of raw materials of vegetable origin associated with the substances isolated were used in 91 cases (1.0%) and homemade teas were used in116 cases (1.2%).…”
Section: Ethno-epidemiological Study Of Pregnant Womencontrasting
confidence: 76%
“…With respect to the use of alternative therapies, 31.0% of pregnant women in Brum et al (2011) and 30.9% in Araújo et al (2016) reported the use of medicinal plants, whereas in our study this was 26.6%resulting in an average of 0.5 medicinal plants being used by the pregnant women. In a study by Mengue et al (2001), phytotherapics were used in 55 cases (0.6%), products composed of raw materials of vegetable origin associated with the substances isolated were used in 91 cases (1.0%) and homemade teas were used in116 cases (1.2%).…”
Section: Ethno-epidemiological Study Of Pregnant Womencontrasting
confidence: 76%
“…For instance, excessive supplementation with vitamin E during pregnancy is related to heart defects (Smedts et al, 2009). Medicinal plants such as fenugreek ( Trigonella foenum-graecum L.), commonly used during pregnancy (de Araújo et al, 2016), is a human teratogen (Taloubi et al, 2013). Worldwide, the use of natural products for primary health care has increased during the last decade (Ekor, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although MPs were used less frequently by our sample, a study in Northeastern Brazil recorded a high prevalence regarding the use of this form of therapy. Peumus boldus, Melissa officinalis, Matricaria chamomilla, and Mentha piperita L. have abortifacient and teratogenic properties and were reported by Araújo et al as frequently used MPs by pregnant women in Brazil (Araújo et al, 2016). It is important to highlight ; Pantoprazole, metformin, tramadol, bromopride, amoxicillin, dexamethasone, metoclopramide, tranexamic acid, zolpidem, and cyclobenzaprine, 1 (0.9%) (each).…”
Section: Discussionmentioning
confidence: 96%